2016
DOI: 10.5037/jomr.2016.7304
|View full text |Cite
|
Sign up to set email alerts
|

The Prosthetic Influence and Biomechanics on Peri-Implant Strain: a Systematic Literature Review of Finite Element Studies

Abstract: ObjectivesTo systematically review risks of mechanical impact on peri-implant strain and prosthetic influence on stability across finite element studies.Material and MethodsAn online literature search was performed on MEDLINE and EMBASE databases published between 2011 and 2016. Following keywords tiered screening and selection of the title, abstract and full-text were performed. Studies of finite element analysis (FEA) were considered for inclusion that were written in English and revealed stress concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 58 publications
4
46
0
2
Order By: Relevance
“…As the manufacturing error was isolated from all other variables, such as the impression‐making and CAD phases, the data give an idea of the influence of a particular type of manufacturing technology on the trueness of the digital workflow used to make full‐arch framework prostheses. The effect of the 3 manufacturing approaches on the framework precision is of paramount importance, to achieve the least misfit possible at the interface of implant platform with the framework . The results of this study showed 3D mean position errors ranging from 8 to 35 µm, similar to previous studies that reported 10 to 51 µm inaccuracy values .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As the manufacturing error was isolated from all other variables, such as the impression‐making and CAD phases, the data give an idea of the influence of a particular type of manufacturing technology on the trueness of the digital workflow used to make full‐arch framework prostheses. The effect of the 3 manufacturing approaches on the framework precision is of paramount importance, to achieve the least misfit possible at the interface of implant platform with the framework . The results of this study showed 3D mean position errors ranging from 8 to 35 µm, similar to previous studies that reported 10 to 51 µm inaccuracy values .…”
Section: Discussionsupporting
confidence: 83%
“…Nonetheless, the 3D errors recorded for both the SLM/m hybrid (8‐22 µm) and milled technologies (20‐35 µm) confirmed that the trueness levels observed here were well within the clinically acceptable limit in terms of dimensional gap, thus attesting to the clinical applicability of all of the manufacturing technologies . The clinical implication of this finding is related to the abovementioned concept of the misfit of the framework at the PFIs that may generate high stresses during clinical screw tightening …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Another significant finding was the association between restorations that were asymmetrical mesio-distally with respect to the fixture and peri-implantitis. While there is evidence in the literature to support association between peri-implantitis and cantilevered prosthesis (Koyano & Esaki, 2015;Maminskas, Puisys, Kuoppala, Raustia, & Juodzbalys, 2016), we believe that this is the first time offset crowns have been identified as putative predictors of periimplantitis. Structurally, asymmetrical crowns can create areas of increased plaque retention due to altered emergence profiles (Katafuchi et al, 2018), while functionally they cause aberrant occlusal load.…”
Section: Discussionmentioning
confidence: 63%
“…The Prosthetic Influence and Biomechanics on Peri-Implant Strain: a Systematic Literature Review of Finite Element Studies (Maminskas et al [3]) …”
Section: Resultsmentioning
confidence: 99%